Cariogenic Antibacterial Potential of Stevia rebaudiana Bertoni Leaves Extract Against Lactobacillus acidophilus - Sinta Deviyanti (Nusantara Science and Technology Proceedings, 2022)
Dental caries is a chronic infectious disease in hard tooth tissues with various factors etiology. The prevalence of dental caries in Indonesia is relatively high. One of the factors of dental caries etiology is cariogenic bacteria known as Lactobacillus acidophilus. These type of bacteria is acidogenic, aciduric, and can adhere to tooth enamel by synthesizing sticky glucan from sucrose to form dental biofilms. The existence of these bacteria in saliva proved to be contributing to the frequency and activity of dental caries, therefore it is important to inhibit their growth to prevent caries. Stevia rebaudiana Bertoni leaves extract is now being developed as an alternative to overcome the problems that are still encountered with the chlorhexidine, as the gold standard for controlling dental biofilms. The review aims to explain the cariogenic antibacterial potential of Stevia rebaudiana Bertoni leaves extract against Lactobacillus acidophilus. Literature search was carried out with sources from the EBSCO, PubMed, and ResearchGate database from the year 2012 to 2022 employing relevant keywords akin to the article titles. Antibacterial activity of Stevia rebaudiana Bertoni leaves extract in various solvents has been shown to be effective against Lactobacillus acidophilus. In this case, it may be due to the content of bioactive components of Stevia leaves extract, such as flavonoids, alkaloids, saponins, sterols, and tannins. Stevia rebaudiana Bertoni leaaves extract has the potential to inhibit the growth of Lactobacillus acidophilus hence, can be used as a natural alternative antibacterial agent to prevent dental caries